Controlled synthesis and processing of a poly(L-lactide-co-ε- caprolactone) copolymer for biomedical use as an absorbable monofilament surgical suture - Sujitra Ruengdechawiwat (2018)
Poly(L-lactide-co-ε-caprolactone) 75:25% mol, P(LL-co-CL), was synthesized via bulk ring-opening polymerisation (ROP) using a novel tin(II)alkoxide initiator, [Sn(Oct)] 2 DEG, at 130oC for 48 hrs. The effectiveness of this initiator was compared withthe well-known conventional tin(II) octoateinitiator, Sn(Oct) 2 . The P(LL-co-CL) copolymersobtained were characterized using a combination of analytical technique including: nuclear magnetic resonance spectroscopy (NMR), differential scanning calorimetry (DSC), thermogravimetry (TG) and gel permeation chromatography (GPC). The P(LL-co-CL) was melt-spun into monofilament fibres of uniform diameter and smooth surface appearance. Modification of the matrix morphology was then built into the as-spun fibresvia a series of controlled off-line annealing and hot-drawing steps. © (2014) Trans Tech Publications, Switzerland.